The Modern Prometheus: The School Principal as a Mediator Leader for Social Justice and Sustainable Development - Maricela Guzmán Cáceres; Leonardo Oliver Ortiz Flores (Universidad Autónoma de Madrid, 2019)
In the present investigation, we propose to problematize the characterization of the directive leadership in the school surroundings from the theoretical contributions of social justice, which we define as a broad spectrum with three main edges around the construction of the notion of the good and the means to achieve it: justice as equity by Rawls, the capabilities approach of Sen and the critical social justice of Pereira. At the same time, we propose to identify how these edges operate as an axiological framework that guides the Sustainable Development Goals of the 2030 Agenda and, in turn, how these objectives contribute to delimit the indeterminate series of capacities pursued by comprehensive moral doctrines, in a framework of substantive freedom. From this theoretical discussion, we approach the role of the director as a conscious leader of the mediation that exerts between the school and social environment capable of upsetting injustices, from an ethical horizon that refers to the "agent of justice" of Pereira. In view of the challenge posed by this task, we return to the Promethean figure in its tragic-heroic character, in order to warn about the structure and the necessary support strategies in the impulse of all transformative work. In this sense, it is argued that Education for Sustainable Development (EDS) offers a frame of reference at a cognitive, socio-emotional and behavioral level to address cross-cutting issues that affect the classroom from a social justice and sustainable leadership perspective.